2001
DOI: 10.1159/000053954
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Echocardiographic Appearance of Arrhythmogenic Right Ventricle Dysplasia: A Case Report

Abstract: We report a case of arrhythmogenic right ventricular dysplasia (ARVD) diagnosed prenatally by echocardiography at 24 weeks gestation. The 4-chamber view showed a large outpouched area extending from below the tricuspid valve to the insertion of the moderator band; the affected wall appeared thin and akinetic, with absence of flow at color Doppler investigation and no evidence of cardiovascular failure. The size of the outpouched area was unchanged at subsequent controls (25 and 26 weeks gestation) when frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Prenatal onset has been reported in some desmosomal mouse models of ARVC. 13 In human ARVC, the diagnosis might be difficult before the age of 10 years, 1 although cases of ARVC in infants, 43 and even in the embryo, 44 have also been reported. In the present study, we have demonstrated that Rho-kinase deficiency in the embryonic heart resulted in abnormal cardiac development, involving ventricular thinning and reduced cardiac proliferation.…”
Section: Rho-kinase Signaling and Arvc 2181mentioning
confidence: 99%
“…Prenatal onset has been reported in some desmosomal mouse models of ARVC. 13 In human ARVC, the diagnosis might be difficult before the age of 10 years, 1 although cases of ARVC in infants, 43 and even in the embryo, 44 have also been reported. In the present study, we have demonstrated that Rho-kinase deficiency in the embryonic heart resulted in abnormal cardiac development, involving ventricular thinning and reduced cardiac proliferation.…”
Section: Rho-kinase Signaling and Arvc 2181mentioning
confidence: 99%
“…In retrospective studies, primary CMs were categorized either as hypertrophic or nonhypertrophic/dilated phenotypes, with some further differentiating a mixed phenotype, suggesting that a simplifying classification appears to be more accurate and reproducible [ 5 , 6 , 8 ]. However, increased sophistication in ultrasound technologies has proposed a more detailed classification encompassing RCM and isolated NCCM, taking varying prognostic parameters and adapted prenatal genetic testing into account [ 7 , 24 , 25 ]. Consequently, in the absence of standardized guidelines and multiple definitions in use, the distribution of fetal phenotypes remains unclear with a prevalence of HCM varying from 18.0% to 60.0% and of DCM from 11.0% to 72.0%, as the most common subgroups [ 5 , 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though our patient had some of the cardinal features of ARVD 6 (RV dilation/dysfunction and arrhythmia), the diagnosis was only confirmed after the histological findings, as fetal presentation of this disease is rare and literature covering this scope is scarce. 2 …”
Section: Discussionmentioning
confidence: 99%
“… 1 In 30-90% of cases, it is an inherited condition, with an autosomal dominant form of transmission. 2 Disease expression is variable. In this article, we discuss a rare case of fetal ARVD and its difficult prenatal diagnosis, only confirmed at post-natal autopsy.…”
Section: Introductionmentioning
confidence: 99%